Análisis de la asociación de campesinos de desarrollo integral Pijullo durante los años 2017 y 2018 - Espinoza Carrera, Gloria Jacinta (2019)
The Association of Farmers of Integral Development Pijullo is currently operating in legal and due form, It has 90 partners in the which each partner has 80 blocks of land for perform the culture of corn. The objective of this work is to verify how is the association economically, which we realize that the same partners turn to sell their products to other businesses because certain seasons the price of corn falls, since when selling at a low price, I would get some loss, which they preferred keep it in storage until it normalizes, having too much time makes lose quality, which runs the danger that is rejected by the client at the time of selling it. Also does not have enough cash to be able to settle your debts in the short term and that the payments he owns, he does not make on time